Lightweight low-thermal-conductivity blocky mullite aerogel material and preparation method thereof

By using the method of combining carbon sacrificial SiOC network and nanoseed crystals with mullite particles in mullite aerogel materials, the problems of high mullite conversion temperature, coarse framework and high thermal conductivity are solved, and the low conversion temperature and low thermal conductivity of the material are achieved, and its potential in high-temperature applications is expanded.

CN119633699APending Publication Date: 2025-03-18AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411829891.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The mullite conversion temperature of existing mullite aerogel materials is relatively high, the coarse skeleton grains, and high thermal conductivity, which limits its wide application in high-temperature heat insulation, catalysis and adsorption.

Method used

The method of recombining carbon sacrificial SiOC network, nanoseed crystals and mullite particles three-dimensional network is adopted to reduce the mullite conversion temperature and improve the integrity of the skeleton and the low thermal conductivity performance through low temperature heat treatment and the formation of carbon sacrificial SiOC network.

Benefits of technology

It has achieved low crystallization temperature, low density, excellent high-temperature anti-oxidation and low thermal conductivity of mullite aerogel materials, and expanded its application prospects in the fields of high-temperature heat insulation, catalysis and adsorption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633699A_ABST
    Figure CN119633699A_ABST
Patent Text Reader

Abstract

The invention discloses a lightweight low-thermal-conductivity blocky mullite aerogel material and a preparation method thereof. The light low-heat-conduction blocky mullite aerogel material comprises a carbon sacrificial SiOC network and a nanometer seed crystal and mullite particle three-dimensional network. The preparation method comprises the following steps: preparing silicon-aluminum composite sol; preparing a Si-O-C precursor sol; uniformly mixing the silicon-aluminum composite sol with the Si-O-C precursor sol to obtain a silicon-aluminum modified composite sol; adding a coagulant into the silicon-aluminum modified composite sol for gelling and aging to obtain SiOC / silicon-aluminum composite gel; carrying out alcohol replacement and supercritical drying treatment on the SiOC / silicon-aluminum composite gel to obtain silicon-aluminum modified composite aerogel; and carrying out heat treatment on the silicon-aluminum modified composite aerogel to obtain the blocky mullite aerogel material. The light low-heat-conduction blocky mullite aerogel material has great application prospects in the fields of high-temperature heat insulation, industrial high-temperature catalysis or adsorption and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of preparation technology of aerogel materials, and in particular to a lightweight and low thermal conductivity mullite aerogel material and a preparation method thereof. Background Art

[0002] Aerogel is an excellent nanoporous thermal insulation material with the characteristics of ultra-light, high porosity, high specific surface area and low thermal conductivity. It has been successfully used in the fields of thermal insulation, catalysis and adsorption. Among the many aerogel materials, silica and alumina aerogels are the most popular and have been studied more maturely, especially in the field of medium and high temperature thermal insulation. Due to the high activity of silica and alumina aerogel nanoparticles, they are prone to obvious sintering and volume shrinkage in the temperature environment of 650℃ and 1000℃, respectively, and the thermal conductivity rises sharply. The material cannot be used stably and will face failure problems in the environment of >1200℃. Compared with silica and alumina aerogels, mullite aerogel has better temperature resistance and has great application potential in higher temperature thermal insulation, catalysis and other fields. During the synthesis and preparation process, due to the high activity of alumina and silica nanoparticles, sintering is easy to occur in high temperature environment, accompanied by a decrease in specific surface area, volume shrinkage and collapse of pore structure. At present, there are few studies and reports on mullite aerogel materials.

[0003] CN 110078425 A, CN201910954101.5 and CN 116425561 A prepared mullite fiber aerogel materials. The obtained materials have excellent properties and performances such as light weight, high porosity, high temperature resistance, heat insulation and heat preservation, and the preparation process is relatively simple. After the material undergoes a heat treatment process, the micron-scale skeleton shrinks and can maintain a relatively regular morphology. However, the raw material is mainly mullite fiber, and the fiber is prepared by a spinning method with low output efficiency, which makes it difficult to achieve large-scale industrial production. Patent CN115974539 B discloses a method for preparing a carbon-mullite aerogel composite material, and proposes to introduce a phenolic resin network into the Al2O3-SiO2 aerogel network to improve the material strength. After a high-temperature heat treatment process in an argon atmosphere (>1200°C), the aluminum oxide and silicon oxide nanoparticles react to transform into mullite particles, and the phenolic resin network transforms into a carbon network. The microstructure of the resulting aerogel presents a typical "pearl necklace" nanostructure, with a compressive strength of up to 15.5MPa. However, the mullite crystal transformation temperature is too high, resulting in larger skeleton particles, and a significant upward trend in thermal conductivity and density (0.07W / (m·K)). In addition, the material system contains a large amount of carbon components, and the material's antioxidant properties are weak, which hinders its application under extremely high temperature oxygen-containing conditions (>800°C). Patent CN 114132940 B discloses a method for preparing high-temperature resistant mullite aerogel, using an aluminum-containing two-dimensional porous, crystalline metal covalent organic framework material as an aluminum source, and using freeze drying to prepare mullite aerogel by 1200°C air calcination. The material has a complete structure and ultra-low density (26mg / cm 3 ), thermal conductivity is not mentioned, but the heat treatment temperature required for mullite in the system is still high, resulting in larger mullite skeleton particles and smaller specific surface area, and the pore size formed by the freeze-drying method is highly connected and large, with poor thermal insulation performance, and the aluminum source used is extremely expensive, making it difficult to mass produce and apply. Therefore, it is urgent to develop a mullite aerogel material with low mullite crystal transformation temperature, low thermal conductivity and high strength. Summary of the invention

[0004] In view of the problems that the current mullite aerogel materials have, such as high mullite transformation temperature, coarsened skeleton grains, and high thermal conductivity, the object of the present invention is to provide a method for preparing a mullite aerogel material. The mullite aerogel material obtained by the preparation method has low transformation temperature, low density, excellent high-temperature oxidation resistance, and low thermal conductivity, and has broad application prospects in the fields of high-temperature thermal insulation, catalysis, adsorption, etc.

[0005] Another object of the present invention is to provide a mullite aerogel material, which is a composite of a carbon sacrificial SiOC network, nano seed crystals and a mullite particle three-dimensional network.

[0006] The purpose of the present invention is achieved through the following technical solutions.

[0007] A lightweight, low-thermal-conductivity bulk mullite aerogel material is composited by a carbon sacrificial SiOC network, nano-seed crystals and a three-dimensional network of mullite particles. The carbon sacrificial SiOC network is a skeleton structure left after carbon in SiOC is oxidized and removed.

[0008] In the above technical solution, the material of the nano seed crystal is aluminum oxide, and the size is 10nm to 150nm.

[0009] In the above solution, the size of the mullite particles is 35 to 200 nm, preferably 40 to 90 nm.

[0010] A method for preparing a lightweight, low thermal conductivity blocky mullite aerogel comprises the following steps:

[0011] preparing a silicon-aluminum composite sol;

[0012] preparing Si-OC precursor sol;

[0013] The silicon-aluminum composite sol and the Si-OC precursor sol are uniformly mixed to obtain a silicon-aluminum modified composite sol;

[0014] Adding a coagulant to the silica-alumina modified composite sol to perform gelation and aging to obtain a SiOC / silica-alumina composite gel;

[0015] The SiOC / silicon-aluminum composite gel is subjected to alcohol replacement and supercritical drying to obtain a silicon-aluminum modified composite aerogel;

[0016] The silicon-aluminum modified composite aerogel is heat-treated to obtain a blocky mullite aerogel material.

[0017] Each step in the above method is described in detail below.

[0018] Step 1, preparation of silicon-aluminum composite sol;

[0019] First, the alcohol solvent is heated to a certain temperature by a heating device, and an aluminum alkoxide precursor is added. After being stirred at a constant temperature for a certain period of time to clarify it, an aluminum sol is obtained; then a certain amount of a silicon precursor is added, and after being fully stirred, an acid catalyst is added dropwise, and finally a certain amount of seed crystals are added. After ultrasonic treatment and full stirring, a silicon-aluminum composite sol is prepared.

[0020] In the step 1, the alcohol solvent is any one of isopropanol, ethanol or n-butanol, the heating temperature is 30 to 70° C., and the constant temperature stirring time is 6 to 24 hours.

[0021] In the step 1, the aluminum alkoxide is any one of aluminum sec-butoxide and aluminum isopropoxide, and the mass ratio of the aluminum alkoxide to the alcohol solvent is (1-4):10.

[0022] In step 1, the silicon precursor is at least one of tetraethyl silicate, tetramethyl silicate, tetrabutyl silicate, tetraphenyl silicate, and tetraisopropyl silicate.

[0023] In the step 1, the molar ratio of the aluminum alkoxide to the silicon precursor is (1-3):1.

[0024] In step 1, the acid catalyst is HNO3 solution or CH3COOH solution, the molar concentration of the acid catalyst is 0.5-4 mol / L, the molar ratio of the acid catalyst to the aluminum alkoxide is (1-1.5):2, and the stirring time after adding the silicon precursor is 8-24 hours.

[0025] In the step 1, the seed crystals include one of α-Al2O3 seed crystals, β-Al2O3 seed crystals, γ-Al2O3 seed crystals and θ-Al2O3 seed crystals or a mixture thereof, and the particle size of the Al2O3 seed crystals is 10 to 100 nm.

[0026] In the step 1, the molar ratio of the Al2O3 seed crystal to the aluminum alkoxide is (0.05-20):100.

[0027] In step 1, the ultrasonic treatment time is 10 to 60 minutes, and the stirring time after adding the seed crystal is 8 to 24 hours.

[0028] Step 2, preparation of Si-OC precursor sol;

[0029] Anhydrous ethanol, deionized water and N, N-dimethylformamide are uniformly mixed, a certain amount of methyltrimethoxysilane and vinyltriethoxysilane silicon precursors are added and fully stirred, and then glacial acetic acid is added to adjust the pH value, and after constant temperature stirring and hydrolysis under certain temperature conditions, Si-OC precursor sol is obtained.

[0030] In step 2, the volume ratio of anhydrous ethanol, deionized water and N,N-dimethylformamide is 30:(2-10):(1-2).

[0031] In step 2, the volume ratio of the methyltrimethoxysilane and vinyltriethoxysilane to the solvent (a mixed solution of anhydrous ethanol, deionized water and N,N-dimethylformamide) is (2-5):(3-6):10.

[0032] In the step 2, the pH value is 5 to 6, and the hydrolysis time with constant temperature stirring is 6 to 24 hours.

[0033] Step 3, preparation of Si-OC / Al2O3-SiO2 wet gel;

[0034] This step is to mix the silica-alumina composite sol prepared in step 1 with the Si-OC precursor sol to obtain a silica-alumina modified composite sol, add a coagulant dropwise to the composite sol to adjust the pH value, then pour the sol into a molding mold, seal it and let it stand to obtain a Si-OC / Al2O3-SiO2 wet gel.

[0035] In the step 3, the volume ratio of the silicon-aluminum composite sol to the Si-OC precursor sol is (1-4):1.

[0036] In step 3, the coagulant is one or a mixture of two of ammonia water, propylene oxide or epichlorohydrin.

[0037] In the step 3, the pH value is 9-10.

[0038] In step 3, the sealing is left to stand for 5 to 24 hours.

[0039] Step 4, preparation of Si-OC / Al2O3-SiO2 aerogel:

[0040] The wet gel block in step 3 is added with an aging liquid, and replaced in an oven at 30-75° C. for 5-14 times, with each aging time being 24 hours, to obtain a gel block; the obtained gel block is taken out from the aging liquid, replaced with alcohol, and then placed in an autoclave, heated and pressurized for supercritical drying to prepare a high-strength block silicon-aluminum composite aerogel.

[0041] In step 4, the aging liquid is one of ethanol, methanol, acetone, or isopropanol, or a mixture thereof.

[0042] In step 4, the supercritical drying method is a carbon dioxide supercritical drying method: carbon dioxide is used as the drying medium, the reaction temperature is 40-65° C., the pressure in the high-pressure reactor is 8-13 MPa, the degassing rate is 3-16 L / min, and the drying time is 7-24 h.

[0043] Step 5, preparation of mullite aerogel material:

[0044] The Si-OC / Al2O3-SiO2 aerogel obtained in step 4 is heat treated in an argon atmosphere to prepare a bulk SiOC / mullite composite aerogel material, which is then calcined in a static air atmosphere to finally obtain a mullite aerogel material. After calcination, a carbon sacrificial SiOC network is formed and composited with the nano seed crystal and the mullite particle three-dimensional network.

[0045] In step 5, the argon atmosphere heat treatment temperature is 1000-1100° C., the heating rate is 2-8° C. / min, and the heat preservation time is 1-4 hours.

[0046] In step 5, the air atmosphere heat treatment temperature is 800-900° C., the heating rate is 2-8° C. / min, and the heat preservation time is 1-4 hours.

[0047] The light-weight and low-thermal-conductivity mullite aerogel material obtained by the preparation method is disclosed.

[0048] The above-mentioned lightweight and low thermal conductivity mullite aerogel material is used in high-temperature insulation, industrial high-temperature catalysis or adsorption materials.

[0049] Compared with the prior art, the present invention has the following advantages:

[0050] (1) Mullite has a low crystallization temperature. In this patent, alumina nano-seed crystals are introduced into the single-phase mullite sol. On the one hand, it can significantly increase the nucleation density and nucleation sites of α-Al2O3 and quickly induce alumina to directly transform from amorphous state to α-Al2O3, thereby reducing the temperature of Al2O3 phase transformation; on the other hand, it reduces the defect vacancy structure generated during the phase transformation of alumina, making the aerogel skeleton stronger. On the basis of the single-phase mullite sol with a low crystallization temperature, thanks to the low-temperature phase transformation and stable structure of alumina, α-Al2O3 aluminum source can be obtained at a lower temperature. Based on the "double mechanism" of low-temperature crystallization, mullite aerogel materials can be prepared at a lower temperature (1000°C). The "double mechanism" refers to the joint action mechanism of nano-seed crystals and single-phase mullite sol.

[0051] (2) Complete skeleton. Based on the "dual mechanism" of low-temperature crystallization, the amorphous SiOC network is introduced. When the silicon source and aluminum source undergo mullite reaction, the grains can be refined and the skeleton shrinks less, thus finally producing ultra-light and low thermal conductivity block mullite aerogel materials.

[0052] (3) The mullite aerogel material prepared by this method is in a complete block, which further reduces the sintering temperature and improves the temperature resistance of the oxide aerogel. In addition, the raw materials are easily available and the preparation process is simple, which is conducive to industrial production. This has positive significance for realizing the application of mullite aerogel materials in high-temperature insulation, industrial high-temperature catalysis or adsorption materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0054] Figure 1The present invention provides a process roadmap for preparing the lightweight and low thermal conductivity mullite aerogel material.

[0055] Figure 2 The figures are actual pictures of the mullite aerogel material prepared in Example 1, wherein (a) is a actual picture of the SiOC / mullite composite aerogel material (SiOC / mullite) after heat treatment in argon atmosphere and before heat treatment in air atmosphere; and (b) is a actual picture of the mullite aerogel material finally prepared by the method of the present invention.

[0056] Figure 3 The figures are scanning electron microscope pictures, wherein (a) is a scanning electron microscope picture of SiOC / mullite composite aerogel material (SiOC / mullite); and (b) is a scanning electron microscope picture of the mullite aerogel material after carbon removal finally prepared by the method of the present invention. DETAILED DESCRIPTION

[0057] It should be noted that the following detailed descriptions are all illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0058] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations and / or combinations thereof.

[0059] The present invention provides a method for preparing a lightweight, low thermal conductivity blocky mullite aerogel material, the process of which is as follows: Figure 1 As shown, the main steps include: preparing a silica-alumina composite sol; preparing a Si-OC precursor sol; uniformly mixing the silica-alumina composite sol with the Si-OC precursor sol to obtain a silica-alumina modified composite sol; adding a coagulant to the silica-alumina modified composite sol for gelation and aging to obtain a SiOC / silicon-alumina composite gel; subjecting the SiOC / silicon-alumina composite gel to alcohol replacement and supercritical drying to obtain a silica-alumina modified composite aerogel; and heat-treating the silica-alumina modified composite aerogel to obtain a blocky mullite aerogel material.

[0060] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.

[0061] The models of the instruments involved in the following embodiments are as follows: 5.0 kV field emission scanning electron microscope (SEM, TDCLS-S4800, Japan), universal testing machine (CMT4303, Meister Industrial Systems, China), specific surface area and pore size analyzer (Nova 2200e, Quanta-chrome Instruments, USA), thermal conductivity tester (TC3000, XIATECH Instrument, China)

[0062] Embodiment 1:

[0063] The ingredients are prepared according to the molar ratio of (molar amount of α-Al2O3 seed crystals): (molar amount of isopropanol) = 1:10 and the volume ratio of Si-OC sol: silicon-aluminum composite sol = 1:3.

[0064] 40g of ethanol was heated to 45°C by a heating device, 4g of aluminum isopropoxide was added, and the mixture was stirred at a constant temperature for 15h to clarify the mixture to obtain an aluminum sol. Subsequently, 1.44g of tetraethyl orthosilicate was added and the mixture was stirred for 5h to obtain a uniform sol. Then, 3mL of CH3COOH solution (1.5mol / L) was added dropwise, and finally 0.3g of α-Al2O3 seed crystals was added. The mixture was ultrasonically treated for 30min and stirred for 1h to obtain a silicon-aluminum composite sol. 30mL of anhydrous ethanol, 6mL of deionized water and 1.5mL of N,N-dimethylformamide were mixed evenly, 10mL of methyltrimethoxysilane and 8mL of vinyltriethoxysilane silicon precursor were added and stirred thoroughly, then glacial acetic acid was added to adjust the pH value to 6, and after stirring at room temperature for 10h for hydrolysis, Si-OC precursor sol was obtained; 10mL of Si-OC precursor sol was added to 30mL of silicon-aluminum composite sol, magnetic stirring was performed for 2h to mix evenly, and ammonia water was added to adjust the pH value to 9 to obtain Si-OC / silicon-aluminum composite sol. Then the sol was poured into a molding mold, sealed and allowed to stand to obtain Si-OC / Al2O3-SiO2 wet gel. After the gel was placed for 3h, ethanol aging solution was added and replaced in an oven at 450℃ for 6 times, each time for 12h. Then the wet gel was replaced by alcohol and subjected to CO2 supercritical drying treatment, and the supercritical reaction temperature was 50℃. The reactor pressure was 10MPa, the degassing rate was 5L / min, and the drying time was 12h to obtain a bulk Si-OC / Al2O3-SiO2 composite aerogel. The Si-OC / Al2O3-SiO2 aerogel was heat treated at 1000℃ in an argon atmosphere, with a heating rate of 4℃ / min and a holding time of 2h, and then calcined at 800℃ in a static air atmosphere, with a heating rate of 10℃ / min and a holding time of 2h, and finally a mullite aerogel material was prepared.

[0065] After testing, the density of the block-shaped lightweight and low thermal conductivity mullite aerogel material is 0.056g / cm 3 , with a specific surface area of ​​263m 2 / g, and the room temperature thermal conductivity is 0.028W·m -1 ·K -1 , compressive strength is 1.28MPa, and temperature resistance can reach 1400℃.

[0066] from Figure 2 It can be seen that after heat treatment, the shape of the obtained mullite aerogel material is controllable and no sintering shrinkage occurs. Figure 3 It can be seen that the aerogel structure presents a typical pearl chain structure and the pore structure is relatively evenly distributed.

[0067] Embodiment 2:

[0068] The ingredients are prepared according to the molar ratio of (molar amount of α-Al2O3 seed crystals): (molar amount of isopropanol) = 1:20.

[0069] 40g of ethanol was heated to 45°C by a heating device, 4g of aluminum isopropoxide was added, and the mixture was stirred at a constant temperature for 15h to clarify the mixture to obtain an aluminum sol. Subsequently, 1.44g of tetraethyl orthosilicate was added and the mixture was stirred for 5h to make the sol uniform. Then, 3mL of CH3COOH solution (1.5mol / L) was added dropwise, and finally 0.15g of α-Al2O3 seed crystals was added. The mixture was ultrasonically treated for 30min and stirred for 1h to obtain a silicon-aluminum composite sol. 30mL of anhydrous ethanol, 6mL of deionized water and 1.5mL of N,N-dimethylformamide were mixed evenly, 10mL of methyltrimethoxysilane and 8mL of vinyltriethoxysilane silicon precursor were added and stirred thoroughly, then glacial acetic acid was added to adjust the pH value to 6, and after stirring at room temperature for 10h for hydrolysis, Si-OC precursor sol was obtained; 10mL of Si-OC precursor sol was added to 30mL of silicon-aluminum composite sol, magnetic stirring was performed for 2h to mix evenly, and ammonia water was added to adjust the pH value to 9 to obtain Si-OC / silicon-aluminum composite sol. Then the sol was poured into a molding mold, sealed and allowed to stand to obtain Si-OC / Al2O3-SiO2 wet gel. After the gel was placed for 3h, ethanol aging solution was added and replaced in an oven at 450℃ for 6 times, each time for 12h. Then the wet gel was replaced by alcohol and subjected to CO2 supercritical drying treatment, and the supercritical reaction temperature was 50℃. The reactor pressure was 10MPa, the degassing rate was 5L / min, and the drying time was 12h to obtain a bulk Si-OC / Al2O3-SiO2 composite aerogel. The Si-OC / Al2O3-SiO2 aerogel was heat treated at 1000℃ in an argon atmosphere, with a heating rate of 4℃ / min and a holding time of 2h, and then calcined at 800℃ in a static air atmosphere, with a heating rate of 10℃ / min and a holding time of 2h, and finally a mullite aerogel material was prepared.

[0070] After testing, the density of the block-shaped lightweight and low thermal conductivity mullite aerogel material is 0.067g / cm 3 , with a specific surface area of ​​253m 2 / g, and the room temperature thermal conductivity is 0.031 W·m -1 ·K -1 , the compressive strength is 0.87MPa.

[0071] Embodiment 3:

[0072] The ingredients are prepared in a volume ratio of Si-OC sol: silicon-aluminum composite sol = 1:6.

[0073] 40g of ethanol was heated to 45°C by a heating device, 4g of aluminum isopropoxide was added, and the mixture was stirred at a constant temperature for 15h to clarify the mixture to obtain an aluminum sol. Subsequently, 1.44g of tetraethyl orthosilicate was added and the mixture was stirred for 5h to obtain a uniform sol. Then, 3mL of CH3COOH solution (1.5mol / L) was added dropwise, and finally 0.3g of α-Al2O3 seed crystals was added. The mixture was ultrasonically treated for 30min and stirred for 1h to obtain a silicon-aluminum composite sol. 30mL of anhydrous ethanol, 6mL of deionized water and 1.5mL of N,N-dimethylformamide were mixed evenly, 10mL of methyltrimethoxysilane and 8mL of vinyltriethoxysilane silicon precursor were added and stirred thoroughly, then glacial acetic acid was added to adjust the pH value to 6, and after stirring at room temperature for 10h for hydrolysis, Si-OC precursor sol was obtained; 5mL of Si-OC precursor sol was added to 30mL of silica-alumina composite sol, magnetically stirred for 2h to mix evenly, and then ammonia water was added to adjust the pH value to 9 to obtain Si-OC / silicon-alumina composite sol. Then the sol was poured into a molding mold, sealed and allowed to stand to obtain Si-OC / Al2O3-SiO2 wet gel. After the gel was placed for 3h, ethanol aging solution was added and replaced in an oven at 450℃ for 6 times, each time for 12h. Then the wet gel was replaced by alcohol and subjected to CO2 supercritical drying treatment, and the supercritical reaction temperature was 50℃. The reactor pressure was 10MPa, the degassing rate was 5L / min, and the drying time was 12h to obtain a bulk Si-OC / Al2O3-SiO2 composite aerogel. The Si-OC / Al2O3-SiO2 aerogel was heat treated at 1000℃ in an argon atmosphere, with a heating rate of 4℃ / min and a holding time of 2h, and then calcined at 800℃ in a static air atmosphere, with a heating rate of 10℃ / min and a holding time of 2h, and finally a mullite aerogel material was prepared.

[0074] After testing, the density of the block-shaped lightweight and low thermal conductivity mullite aerogel material is 0.078g / cm 3 , with a specific surface area of ​​156m 2 / g, and the room temperature thermal conductivity is 0.032W·m -1 ·K -1 , compressive strength is 1.89MPa, and temperature resistance can reach 1400℃.

[0075] Embodiment 4:

[0076] No Si-OC sol was added for batching.

[0077] 40g of ethanol was heated to 45℃ by a heating device, 4g of aluminum isopropoxide was added, and the mixture was stirred at a constant temperature for 15h until it was clarified to obtain aluminum sol. Subsequently, 1.44g of tetraethyl orthosilicate was added, and the mixture was stirred for 5h until the sol was uniform. Then, 3mL of CH3COOH solution (1.5mol / L) was added dropwise, and finally 0.3g of α-Al2O3 seed crystals were added. The mixture was ultrasonically treated for 30min and stirred for 1h to obtain a silicon-aluminum composite sol. Ammonia water was added to adjust the pH value to 9, and the sol was then poured into a molding mold, sealed and allowed to stand to obtain Al2O3-SiO2 wet gel. After the gel was placed for 3h, ethanol aging solution was added and replaced in an oven at 450℃ for 6 times, each time for 12h. The wet gel was then replaced with alcohol and subjected to CO2 supercritical drying treatment, with a supercritical reaction temperature of 50℃. The reactor pressure was 10MPa, the degassing rate was 5L / min, and the drying time was 12h to obtain a bulk Al2O3-SiO2 composite aerogel. The Al2O3-SiO2 aerogel was heat treated at 1000℃ in an argon atmosphere, with a heating rate of 4℃ / min and a holding time of 2h, and then calcined at 800℃ in a static air atmosphere, with a heating rate of 10℃ / min and a holding time of 2h, and finally a mullite aerogel material was prepared.

[0078] After testing, the density of the block-shaped lightweight and low thermal conductivity mullite aerogel material is 0.12g / cm 3 , with a specific surface area of ​​89m 2 / g, and the room temperature thermal conductivity is 0.067W·m -1 ·K -1 , the compressive strength is 3.65MPa.

[0079] Embodiment 5:

[0080] The heat treatment temperature in an argon atmosphere is 900°C.

[0081] 40g of ethanol was heated to 45°C by a heating device, 4g of aluminum isopropoxide was added, and the mixture was stirred at a constant temperature for 15h to clarify the mixture to obtain an aluminum sol. Subsequently, 1.44g of tetraethyl orthosilicate was added and the mixture was stirred for 5h to obtain a uniform sol. Then, 3mL of CH3COOH solution (1.5mol / L) was added dropwise, and finally 0.3g of α-Al2O3 seed crystals was added. The mixture was ultrasonically treated for 30min and stirred for 1h to obtain a silicon-aluminum composite sol. 30mL of anhydrous ethanol, 6mL of deionized water and 1.5mL of N,N-dimethylformamide were mixed evenly, 10mL of methyltrimethoxysilane and 8mL of vinyltriethoxysilane silicon precursor were added and stirred thoroughly, then glacial acetic acid was added to adjust the pH value to 6, and after stirring at room temperature for 10h for hydrolysis, Si-OC precursor sol was obtained; 10mL of Si-OC precursor sol was added to 30mL of silicon-aluminum composite sol, magnetic stirring was performed for 2h to mix evenly, and ammonia water was added to adjust the pH value to 9 to obtain Si-OC / silicon-aluminum composite sol. Then the sol was poured into a molding mold, sealed and allowed to stand to obtain Si-OC / Al2O3-SiO2 wet gel. After the gel was placed for 3h, ethanol aging solution was added and replaced in an oven at 450℃ for 6 times, each time for 12h. Then the wet gel was replaced by alcohol and subjected to CO2 supercritical drying treatment, and the supercritical reaction temperature was 50℃. The reactor pressure was 10MPa, the degassing rate was 5L / min, and the drying time was 12h to obtain a bulk Si-OC / Al2O3-SiO2 composite aerogel. The Si-OC / Al2O3-SiO2 aerogel was heat treated at 900℃ in an argon atmosphere, with a heating rate of 4℃ / min and a holding time of 2h, and then calcined at 800℃ in a static air atmosphere, with a heating rate of 10℃ / min and a holding time of 2h, and finally a mullite aerogel material was prepared.

[0082] After testing, the density of the block-shaped lightweight and low thermal conductivity mullite aerogel material is 0.045g / cm 3 , with a specific surface area of ​​348m 2 / g, and the room temperature thermal conductivity is 0.025W·m -1 ·K -1 , compressive strength is 0.96MPa, and temperature resistance can reach 1300℃.

[0083] Embodiment 6:

[0084] No alumina seed crystals were added for batching.

[0085] 40g of ethanol was heated to 45°C by a heating device, 4g of aluminum isopropoxide was added, and the mixture was stirred at a constant temperature for 15h until it was clarified to obtain aluminum sol, and then 1.44g of ethyl orthosilicate was added, and the mixture was stirred for 5h until the sol was uniform, and 3mL of CH3COOH solution (1.5mol / L) was added dropwise, and the mixture was stirred for 1h to obtain silicon-aluminum composite sol. 30mL of anhydrous ethanol, 6mL of deionized water and 1.5mL of N,N-dimethylformamide were mixed evenly, 10mL of methyltrimethoxysilane and 8mL of vinyltriethoxysilane silicon precursor were added and stirred well, and then glacial acetic acid was added to adjust the pH value to 6, and after stirring at room temperature for 10h for hydrolysis, Si-OC precursor sol was obtained; 10mL of Si-OC precursor sol was added to 30mL of silicon-aluminum composite sol, and after magnetic stirring for 2h to mix evenly, ammonia water was added to adjust the pH value to 9 to obtain Si-OC / silicon-aluminum composite sol. Then pour the sol into the molding mold, seal it and let it stand to obtain Si-OC / Al2O3-SiO2 wet gel. After the gel is placed for 3 hours, add ethanol aging solution and replace it in an oven at 450℃ for 6 times, each time for 12 hours. Then the wet gel is replaced by alcohol and subjected to CO2 supercritical drying treatment, and the supercritical reaction temperature is 50℃. The reactor pressure is 10MPa, the degassing rate is 5L / min, and the bulk Si-OC / Al2O3-SiO2 composite aerogel is obtained after 12 hours of drying time. The Si-OC / Al2O3-SiO2 aerogel is heat treated at 1000℃ in an argon atmosphere, with a heating rate of 4℃ / min and a holding time of 2h, and then calcined at 800℃ in a static air atmosphere, with a heating rate of 10℃ / min and a holding time of 2h, and finally a mullite aerogel material is prepared.

[0086] After testing, the density of the block-shaped lightweight and low thermal conductivity mullite aerogel material is 0.032g / cm 3 , with a specific surface area of ​​287m 2 / g, and the room temperature thermal conductivity is 0.027W·m -1 ·K -1 , compressive strength is 1.06MPa, and temperature resistance can reach 1300℃.

[0087] Summary: Comparison between Example 1 and Example 2 shows that the effect of the addition ratio of alumina seed crystals as a nucleation regulating material for aerogel on the degree of mullitization is as follows: within a certain range of proportions, the greater the addition ratio, the greater the degree of mullitization, and the higher the compressive strength and temperature resistance; Comparison between Example 1 and Example 3 shows that the effect of the introduction of amorphous SiOC network on the sintering behavior of mullitized grains is as follows: the introduction of amorphous SiOC network refines the mullite skeleton particles, slightly reduces the strength, but improves the thermal insulation performance; Comparison between Example 1 and Example 4 shows that the effect of amorphous SiOC network on the performance of aerogel materials is as follows: amorphous SiO The introduction of C network can maintain the integrity of the aerogel network, inhibit large-scale shrinkage and collapse, and ensure the thermal insulation performance of the aerogel material; in comparison with Example 1 and Example 5, the heat treatment temperatures are different, and the effect of the heat treatment temperature on the performance of the aerogel material is: within a certain temperature range, the higher the temperature, the greater the compressive strength, and the more complete the mullite conversion; in comparison with Example 1 and Example 6, the effect of the addition of alumina seed crystals on the sintering behavior of the composite material is: within a certain range, the more alumina seed crystals are added, the more complete the mullite degree, the smaller the heat treatment shrinkage rate, the higher the compressive strength, and the better the thermal insulation performance.

[0088] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A lightweight, low thermal conductivity blocky mullite aerogel material, characterized in that: The blocky mullite aerogel material is composited by a carbon sacrificial SiOC network, nano seed crystals and a three-dimensional network of mullite particles. The carbon sacrificial SiOC network is a skeleton structure left after carbon in SiOC is oxidized and removed.

2. The lightweight and low thermal conductivity blocky mullite aerogel material according to claim 1, characterized in that: The material of the nano seed crystal is aluminum oxide, and the size is 10nm-150nm; the particle size of the mullite particle is 35-200nm.

3. A method for preparing a lightweight, low thermal conductivity blocky mullite aerogel material, characterized in that: The following steps are involved: preparing a silicon-aluminum composite sol; preparing Si-OC precursor sol; The silicon-aluminum composite sol and the Si-OC precursor sol are uniformly mixed to obtain a silicon-aluminum modified composite sol; Adding a coagulant to the silica-alumina modified composite sol to perform gelation and aging to obtain a SiOC / silica-alumina composite gel; The SiOC / silicon-aluminum composite gel is subjected to alcohol replacement and supercritical drying to obtain a silicon-aluminum modified composite aerogel; The silicon-aluminum modified composite aerogel is heat-treated to obtain a blocky mullite aerogel material.

4. The method according to claim 3, characterized in that The method for preparing the silicon-aluminum composite sol comprises: The alcohol solvent is heated to 30-70° C. by a heating device, an aluminum alkoxide precursor is added, and the mixture is stirred at a temperature of 30-70° C. for 6-24 hours to obtain an aluminum sol after clarification; a silicon precursor is then added, and after being fully stirred, an acid catalyst is added dropwise, and finally a seed crystal is added, and after ultrasonic treatment for 10-60 minutes and fully stirred for 8-24 hours, a silicon-aluminum composite sol is prepared; The alcohol solvent is any one of isopropanol, ethanol or n-butanol; the aluminum alkoxide is any one of aluminum sec-butoxide and aluminum isopropoxide, and the mass ratio of the aluminum alkoxide to the alcohol solvent is (1-4):10; The silicon precursor is at least one of tetraethyl silicate, tetramethyl silicate, tetrabutyl silicate, tetraphenyl silicate and tetraisopropyl silicate; the molar ratio of the aluminum alkoxide to the silicon precursor is (1-3):1; The acid catalyst is HNO3 solution or CH3COOH solution, the molar concentration of the acid catalyst is 0.5-4 mol / L, the molar ratio of the acid catalyst to the aluminum alkoxide is (1-1.5):2, and the stirring time after adding the silicon precursor is 8-24h; The seed crystals include one of α-Al2O3 seed crystals, β-Al2O3 seed crystals, γ-Al2O3 seed crystals and θ-Al2O3 seed crystals or a mixture thereof, and the particle size of the seed crystals is 10-100nm; the molar ratio of the Al2O3 seed crystals to aluminum alkoxide is (0.05-20):

100.

5. The method according to claim 4, characterized in that The preparation of Si-OC precursor sol comprises: Anhydrous ethanol, deionized water and N, N-dimethylformamide are uniformly mixed, a certain amount of methyltrimethoxysilane and vinyltriethoxysilane silicon precursors are added and fully stirred, and then glacial acetic acid is added to adjust the pH value, and after constant temperature stirring and hydrolysis under certain temperature conditions, Si-OC precursor sol is obtained; The volume ratio of anhydrous ethanol, deionized water and N,N-dimethylformamide is 30:(2-10):(1-2); The volume ratio of the methyltrimethoxysilane, vinyltriethoxysilane, and the mixed solution of anhydrous ethanol, deionized water and N,N-dimethylformamide is (2-5): (3-6): 10; The pH value is 5 to 6, and the time of constant temperature stirring hydrolysis is 6 to 24 hours.

6. The method according to claim 3, characterized in that The silicon-aluminum composite sol and the Si-OC precursor sol are mixed uniformly, wherein the volume ratio of the silicon-aluminum composite sol to the Si-OC precursor sol is (1-4):

1.

7. The method according to claim 3, characterized in that The step of adding a coagulant to the silica-alumina modified composite sol for gelation and aging comprises: Add a coagulant dropwise to the silica-alumina modified composite sol to adjust the pH value, then pour the sol into a molding mold, seal it and let it stand to obtain a wet gel, add an aging liquid to the wet gel block, and replace it in an oven at 30-75°C for 5-14 times, with each aging time being 24 hours; The coagulant is one or a mixture of two of ammonia water, propylene oxide or epichlorohydrin; The pH value is 9 to 10; The sealing and standing time is 5 to 24 hours; The aging liquid is one of ethanol, methanol, acetone, isopropanol or a mixture thereof.

8. The method according to claim 3, characterized in that The supercritical drying process uses carbon dioxide as a drying medium, the reaction temperature is 40-65° C., the pressure in the high-pressure reactor is 8-13 MPa, the degassing rate is 3-16 L / min, and the drying time is 7-24 h.

9. The method according to claim 3, characterized in that: The heat treatment of the silicon-aluminum modified composite aerogel comprises: The silicon-aluminum modified composite aerogel is heat-treated in an argon atmosphere at a temperature of 1000-1100° C., a heating rate of 2-8° C. / min, and a heat preservation time of 1-4 hours to obtain a block SiOC / mullite composite aerogel material; The bulk SiOC / mullite composite aerogel material is calcined in an air atmosphere, the calcination temperature is 800-900° C., the heating rate is 2-8° C. / min, and the insulation time is 1-4 hours to obtain the bulk mullite aerogel material.

10. Use of the lightweight, low thermal conductivity blocky mullite aerogel material prepared by the method according to any one of claims 3 to 9 in high temperature thermal insulation materials, industrial high temperature catalytic carrier materials or adsorption materials.

Citation Information

Patent Citations

  • Preparation method of light heat-insulating mullite nanofiber aerogel

    CN110078425A

  • Flexible mullite fiber aerogel material and preparation method thereof

    CN110846741A

  • A method for preparing ultralight, high-temperature resistant bulk mullite aerogel

    CN114132940B

  • A method for preparing bulk high-temperature resistant mullite ceramic aerogel

    CN115974539B

  • Preparation method of 3D printing nanofiber / nanosheet ceramic aerogel

    CN116425561A